Energy-efficient retrofit of social housing in the UK: lessons learned from a Community Energy Saving Programme (CESP) in Nottingham - Elsharkawy, Heba; Rutherford, Peter (Elsevier, 2018)
One of the long-term challenges outlined within the UK Government's Energy White Paper (2011) is to cut both greenhouse gas (GHG) emissions and energy bills by improving household energy efficiency. As such, several energy-related initiatives have, in recent years, been promoted including the Community Energy Saving Programme. In this study, we explore how patterns of user consumption as influenced by occupant awareness and behaviour, can both positively and negatively influence policy initiative delivery. In so doing, we present the results from an extensive pre- and post-retrofit home energy use and performance survey of 150 properties located in Nottingham's Aspley ward, home of one of England's pilot CESP schemes. Our results show that whilst this specific initiative significantly improved home conditions and reduced energy consumption, it failed to achieve the predicted £300 annual savings on household energy bills. This was found to be largely attributed to occupants’ ingrained habits towards household energy use, higher comfort level preferences, (lack of) energy consumption awareness, and insufficient information provided to help residents better manage their home energy use following the retrofit. By exploring some of the core lessons learned from the survey, this research seeks to inform and improve the uptake and delivery of future retrofit initiatives.